2017
DOI: 10.1038/s41598-017-07049-3
|View full text |Cite
|
Sign up to set email alerts
|

Shift of EMT gradient in 3D spheroid MSCs for activation of mesenchymal niche function

Abstract: Despite the wide use of mesenchymal stromal cells (MSCs) for paracrine support in clinical trials, their variable and heterogeneous supporting activity pose major challenges. While three-dimensional (3D) MSC cultures are emerging as alternative approaches, key changes in cellular characteristics during 3D-spheroid formation remain unclear. Here, we show that MSCs in 3D spheroids undergo further progression towards the epithelial-mesenchymal transition (EMT), driven by upregulation of EMT-promoting microRNAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
(77 reference statements)
1
17
0
1
Order By: Relevance
“…Accordingly, the BM microenvironment should undergo dynamic changes in niche activity to accommodate the alternating needs for hematopoietic activity. Consistent with this view, we have shown that the mesenchymal cells can undergo reversible changes during cell culture, exhibiting distinct niche activities [29], and that these niche activities are regulated by changes in signals from canonical Wnt or notch ligands, for example [17,30], as well as by the molecular gradient for the epithelial-mesenchymal transition (EMT), as observed in a model for 3-D mesenspheres [31]. However, the dynamic changes in the BM niche in response to varying physiological demands, which reveal how the regenerative process for maintaining body homeostasis is controlled, remains largely unknown.…”
Section: Introductionsupporting
confidence: 62%
“…Accordingly, the BM microenvironment should undergo dynamic changes in niche activity to accommodate the alternating needs for hematopoietic activity. Consistent with this view, we have shown that the mesenchymal cells can undergo reversible changes during cell culture, exhibiting distinct niche activities [29], and that these niche activities are regulated by changes in signals from canonical Wnt or notch ligands, for example [17,30], as well as by the molecular gradient for the epithelial-mesenchymal transition (EMT), as observed in a model for 3-D mesenspheres [31]. However, the dynamic changes in the BM niche in response to varying physiological demands, which reveal how the regenerative process for maintaining body homeostasis is controlled, remains largely unknown.…”
Section: Introductionsupporting
confidence: 62%
“…This study reported a stronger osteogenic potential of CD271-MSCs than the PA-MSCs, but again was based on a 2D study. It is well documented that MSCs grown on 2D or 3D structural compositions have widely different properties [29][30][31], and here we demonstrate that, for our scaffold and cell populations, the differences between 2D and 3D culture can mean that results from 2D culture are a poor predictor of performance on a 3D scaffold. Interestingly, compared to uncultured CD271-enriched BM-MNCs, we observed a higher DNA content and higher ALP activity in native BM-MNCs (unselected and uncultured) when seeded on the A-W scaffold.…”
Section: Discussionmentioning
confidence: 53%
“…Human MSCs are known to constitute a heterogeneous population 8,9,10 . To examine the cellular diversity within the population, hMSCs were first characterized by their expression of membrane markers.…”
Section: Self-organization Of Hmscs In 3d Mesenchymal Bodiesmentioning
confidence: 99%
“…4! related to differentiation, immune-regulation and angiogenesis 8,9,10 . Nonetheless their aggregation leads to the formation of highly cohesive 3D spherical structures (which we designate hereafter as mesenchymal bodies, MBs) with improved biological activities in comparison to 2D cultures 11 .…”
Section: Introductionmentioning
confidence: 99%